1995
DOI: 10.1177/105477389500400309
|View full text |Cite
|
Sign up to set email alerts
|

Hmong Cultural Practices and Beliefs

Abstract: The purpose of this study was to explore the cultural practices and beliefs of the Hmong in the postpartum period. Using the qualitative research method of in-depth interviewing, data were collected through semistructured interviews. A convenience sample of 52 childbearing Hmong women was interviewed with the help of Hmong interpreters. The interviews were audiotaped and transcribed for analysis. Data analysis revealed cultural practices and beliefs categories related to diet, rest period, appropriate clothing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Prescriptive behaviors after childbirth are important for ensuring women's short-term survival, long-term health, maintenance of their fertility, and their ability to produce breast milk . In this study informants rarely reported herbal bathing for postpartum treatments even if 'warm showers/baths' have been reported in other studies of the Hmong postpartum treatments (Jambunathan, 1995). Such herbal bathing is also common among other Thai and Southeast Asian cultures (Liulan et al, 2003;Lundh, 2007;Zumsteg and Weckerle, 2007;de Boer and Lamxay, 2009;Lamxay et al, 2011;Panyaphu et al, 2011).…”
Section: Plants Used For Postpartum Recoverymentioning
confidence: 82%
See 3 more Smart Citations
“…Prescriptive behaviors after childbirth are important for ensuring women's short-term survival, long-term health, maintenance of their fertility, and their ability to produce breast milk . In this study informants rarely reported herbal bathing for postpartum treatments even if 'warm showers/baths' have been reported in other studies of the Hmong postpartum treatments (Jambunathan, 1995). Such herbal bathing is also common among other Thai and Southeast Asian cultures (Liulan et al, 2003;Lundh, 2007;Zumsteg and Weckerle, 2007;de Boer and Lamxay, 2009;Lamxay et al, 2011;Panyaphu et al, 2011).…”
Section: Plants Used For Postpartum Recoverymentioning
confidence: 82%
“…This also holds for the Hmong culture and a rest period of one month after childbirth is commonly recommended (Jambunathan, 1995;Daviau, 2003). Despite the fact that young Hmong mothers no longer give birth at home, postpartum practices are still important and adhered to.…”
Section: Plants Used For Postpartum Recoverymentioning
confidence: 97%
See 2 more Smart Citations
“…Mismanagement of PPH cases often exacerbates morbidity and mortality in resource poor settings due to the absence of antenatal care, inadequacy of primary health care training, inadequate referrals, lack of emergency facilities and equipments, and absence of blood transfusion facilities [25]. those in the biomedical field [26][27][28]. In Nepal, community perceptions of bleeding and the associated meanings vary among different members of the family [29].…”
Section: Introductionmentioning
confidence: 99%